The Routledge handbook of stylistics - Burke, Michael 1964- (London Routledge, 2018)
The Routledge Handbook of Stylistics provides a comprehensive introduction and reference point to key areas in the field of stylistics. The four sections of the volume encompass a wide range of approaches from classical rhetoric to cognitive neuroscience and cover core issues that include: Historical perspectives centring on rhetoric, formalism and functionalism. The elements of stylistic analysis that include the linguistic levels of foregrounding, relevance theory, conversation analysis, narrative, metaphor, speech acts, speech and thought presentation and point of view. Current areas of 'hot topic' research, such as cognitive poetics, corpus stylistics and feminist/critical stylistics. Emerging and future trends including the stylistics of multimodality, creative writing, hypertext fiction and neuroscience. Each of the thirty-two chapters provides: an introduction to the subject; an overview of the history of the topic; an analysis of the main current and critical issues; a section with recommendations for practice, and a discussion of possible future trajectory of the subject. The Routledge Handbook of Stylistics is essential reading for researchers, postgraduates and undergraduate students working in this area.
Rhetoric and poetics: the classical heritage of stylistics / Michael Burke -- Formalist stylistics / Michael Burke and Kristy Evers -- Functionalist stylistics / Patricia Canning -- Reader response criticism and stylistics / Jennifer Riddle Harding -- The linguistic levels of foregrounding in stylistics / Christiana Gregoriou -- (New) historical stylistics / Beatrix Busse -- Stylistics, speech acts and im/politeness theory / Derek Bousfield -- Stylistics, conversation analysis and the cooperative principle / Marina Lambrou -- Stylistics and relevance theory / Billy Clark -- Stylistics, point of view and modality / Clara Neary -- Stylistics and narratology / Dan Shen -- Metaphor and stylistics / Szilvia Csábi -- Speech and thought presentation in stylistics / Joe Bray -- Pedagogical stylistics / Geoff Hall -- Stylistics, drama and performance / Andrea Macrae -- Schema theory in stylistics / Catherine Emmott, Marc Alexander, and Agnes Marszalek -- Stylistics and text world theory / Ernestine Lahey -- Stylistics and blending / Barbara Dancygier -- Cognitive poetics / Margaret H. Freeman -- Quantitative methodological approaches to stylistics / Olivia Fialho and Sonia Zyngier -- Feminist stylistics / Rocío Montoro -- Literary pragmatics and stylistics / Chantelle Warner -- Corpus stylistics / Michaela Mahlberg -- Stylistics and translation / Jean Boase-Beier -- Critical stylistics / Lesley Jeffries -- Creative writing and stylistics / Jeremy Scott -- Stylistics and real readers / David Peplow and Ronald Carter -- Stylistics and film / Michael Toolan -- Multimodality and stylistics / Nina Nørgaard -- Stylistics and comics / Charles Forceville, Elisabeth El Refaie, and Gert Meesters -- Stylistics and hypertext fiction / Paola Trimarco -- Stylistics, emotion and neuroscience / Patrick Colm Hogan.
"Simultaneously published in the USA and Canada by Routledge"--Title page verso.
Includes bibliographical references and index.
Keywords: English language -- Style; English language -- Rhetoric; Literary style